Thành phần hóa học của cây Mussaenda pubescens (Rubiaceae) - Thu Hiền, Lê Thị; Phương Thảo, Lê Thị; Thưởng, Lê Quý; Việt, Trần Quốc; Trung, Đồng Văn (Vietnam Journal of Chemistry, 2017)
The genus Mussaenda is an important source of medicinal natural products, particularly iridoids, triterpenes, saponines and flavonoids. The plants are members of the Rubiaceae and are native to the Old World tropics, from West Africa through the Indian sub-continent, South-East Asia and to Southern China. There are more than 200 species of Mussaenda known. Some species of Mussaenda have been used in traditional medicine. The abundance of the iridoids and its wide availability makes the plant a potential target for studying the activity of this drug. From the water extract of Mussaenda pubescens, six compounds, shanzhiside methylester (1), barlerin (2), mussaenoside (3), (6S, 9R)-roseoside (4), mussaendoside L (5) and coniferin (6) were isolated. Their structures were elucidated by using MS and NMR spectroscopic methods, including 2D NMR spectroscopy (COSY, HMQC, HMBC). Keywords. Mussaenda pubescens, Rubiaceae, iridoid, shanzhiside methylester.